Scientific Opinion on bluetongue serotype 8 - EFSA Panel on Animal Health and Welfare (EFSA Journal, 2011)
Abstract To answer a question from the European Commission on the potential special characteristics of bluetongue virus (BTV) serotype 8 (BTV‐8) compared to other serotypes and their possible impact on the epidemiology of the disease, a systematic literature review was carried out by a working group established by the Animal Health and Welfare Panel. Currently, three special features can be assigned to BTV‐8, which are the ability to cause serious disease in cattle and goats, the ability to be transmitted transplacentally, and the ability to contaminate semen. The transplacental transmission and the contamination of semen are also observed for several serotypes of modified live virus (MLV) vaccines and for some cell culture/egg passaged strains. These two features may have an impact on the epidemiology of the disease, since they may increase the ability of BTV‐8 to survive the winter period, for example, when pregnant cows are infected in late autumn and give birth to viraemic offspring in the next vector season, or, through infecting the recipient dam via artificial insemination (AI) with frozen contaminated semen. Furthermore, the chance of BTV‐8 spread may be increased either through movement of seropositive but virus negative pregnant animals, which may give birth to viraemic calves, or through natural mating or AI using BTV‐8 contaminated semen by transmission from semen to receiving dam. The current legislation provides effective measures to ensure that all dams are immune to BTV before insemination or mating, so there is no subsequent risk of transplacental infection of their offspring. Furthermore, pregnant animals are effectively restricted in their movement. More research is needed to determine whether oral transmission and/or transmission through embryo transfer are more likely to occur for BTV‐8 than for other BTV serotypes.